Split Hopkinson bar tensile testing - Leong, Boaz Jia Hao (2017)
The Split Hopkinson Pressure Bar (SHPB) experiment can be categories into three testing methods; tension, compression and torsion. SHPB tests are used to investigate the mechanical properties of materials tested at different loading conditions under high strain rates. In this paper, only the tension SHPB will be discussed. The tension SHPB test is done to investigate the response of the dynamic stress and strain for different materials under high strain rate conditions from 1000/s to 100000/s. The governing theory is based on the longitudinal pressure wave propagation along the elastic stainless steel bars. Strain gauges are used in the experiment and were mounted on the input and output bars to detect the incidence, reflected and transmitted waves. The data obtained from the oscilloscope is then processed to produce the stress, strain and strain rate responses. In this Tension SHPB project, various tests such as the empty run, calibration and actual tests were carried out to develop and improve on the current Tension SHPB apparatus. The specimen material AL6061-T6 was used throughout the entire project to produce repeatability and consistency in the results obtained. This project furthermore aims to study the mechanical behavior of the specimen under dynamic loading at high strain rates. In addition, to analyze the effects of varying gauge lengths and geometry when under dynamic loading. Lastly, recommendations were proposed to improve the accuracy and quality of the experimental results together with the conclusion of the project.